EDUCATION TO MAINTAIN FRIENDSHIP TO STRENGTHEN THE FOUNDATIONS OF PEACE IN SOCIETY - Fadhillah, Muhammad; Emawati, Emawati; Sulastri, Ema; Yusliani, Hamdi; Rosnidarwati, Rosnidarwati (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2024)
According to Islamic teachings, human beings are connected to each other, and as such, they naturally require the company of other people. Due to their inherent weakness, humans depend on the support of people around them. Thus, it is not unusual to refer to humans as social beings. This is owing to the fact that humans are beings who will always require the company of other people. This suggests that all Muslims have a duty to uphold friendship, whether it is through familial ties (descendants) or brotherly relationships with other Muslims. It is necessary for non-Muslims to uphold the virtue of mutual respect and appreciation, even if they go about it in various ways. It is hard to establish harmony and peace within a society if its people lack affection, as this always results in arguments, animosity, and ultimately, murder. For this reason, shilaturrahim (engaging with others)—both general and specific—are essential to bringing about the world's peace, harmony, and unification of humanity. Keywords: Society, Engagement with others, peace